2009
DOI: 10.1186/cc8193
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum-assisted closure device enhances recovery of critically ill patients following emergency surgical procedures

Abstract: IntroductionCritically ill surgical patients frequently develop intra-abdominal hypertension (IAH) leading to abdominal compartment syndrome (ACS) with subsequent high mortality. We compared two temporary abdominal closure systems (Bogota bag and vacuum-assisted closure (VAC) device) in intra-abdominal pressure (IAP) control.MethodsThis prospective study with a historical control included 66 patients admitted to a medical and surgical intensive care unit (ICU) of a tertiary care referral center (Careggi Hospit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
48
0
5

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 23 publications
2
48
0
5
Order By: Relevance
“…[32] Similarly, the present study revealed a significantly earlier abdominal closure time in the VAC group. Recently, a study by Long and colleagues has evaluated the utility of concomitant therapies for open abdomen by comparing the VAC used in combination with the abdominal re-approximation abdominal wall anchor closure (ABRA) system for closure of open abdomen.…”
Section: Discussionsupporting
confidence: 77%
“…[32] Similarly, the present study revealed a significantly earlier abdominal closure time in the VAC group. Recently, a study by Long and colleagues has evaluated the utility of concomitant therapies for open abdomen by comparing the VAC used in combination with the abdominal re-approximation abdominal wall anchor closure (ABRA) system for closure of open abdomen.…”
Section: Discussionsupporting
confidence: 77%
“…Cytokine levels, tissue ischemia markers, and/or thrombopoietin levels might be studied to further support the hypothesis of Thomas and Boos as mentioned above. Second, the IAP was kept at 12 mmHg during the study, which corresponds to grade I IAH (grade I = IAP 12 to 15 mmHg, grade II = IAP 16 to 20 mmHg, grade III = IAP 21 to 25 mmHg, grade IV = IAP > 25 mmHg) (2,6,29). If the IAP is increased above this level, it is possible that more significant changes in MPV values would be seen.…”
Section: Discussionmentioning
confidence: 99%
“…We described the use of vacuum-assisted dressing (VAC) in the successful management of severe DNM with both involvement of superior and inferior mediastinum. VAC dressing was described commonly in management of complex wound such as osteomyelitis of long bones [10]. It creates negative pressure that helps to remove inflammatory exudates, reduce edema, increase perfusion and promote granulation [11].…”
Section: Discussionmentioning
confidence: 99%